Studi Literatur: Peran Hukum Perdata Internasional dalam Kasus Bisnis Lintas Negara - Elizabet Noviola Panjaitan; Helena Natasya Sipayung; Yazid Aditya Sitorus; Christian Ronaldo Simbolon (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study examines the role of Private International Law (IPL) in resolving various cross-border business issues. The literature review focuses on several case studies, namely the trademark dispute between Prada S.A. and PT. Manggala Putra Perkasa, the imposition of sanctions on cross-border acquisitions, the settlement of furniture export contracts, and the position of official translators in international contracts. The analysis shows that IPL plays a significant role in protecting intellectual property rights, ensuring legal certainty, supporting international business regulations, and ensuring the validity of international contracts. Indonesia needs to strengthen specific regulations, expand legal protection for small and medium enterprises (SMEs), and emphasize the obligation to use sworn translators in cross-border business transactions.